A new life - Malamud, Bernard 1914-1986 (Farrar, Straus and Giroux, 2004)
Sy Levin, a high school teacher beset by alcohol and bad decisions, leaves New York for the Pacific Northwest to start over, imagining that an extraordinary new life awaits him there. Soon after arriving, he realizes that he had fallen for the myth of the West as a place of personal reinvention.
Keywords: College teachers -- Fiction; Northwest, Pacific -- Fiction; Fiktionale Darstellung